Anaerobic Digestion sebagai Inovasi Pengolahan Limbah Cair Industri Tahu untuk Menurunkan Dampak terhadap Kesehatan Lingkungan : Literature Review - Deandra Alifia Isrofi; M.Farid Dimjati Lusno (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
The tofu industry generates wastewater with high organic content that can cause environmental pollution and pose risks to public health if not properly managed. This study is a literature review aimed at analyzing the effectiveness of anaerobic digestion as a sustainable innovation for tofu wastewater treatment. The review findings indicate that anaerobic digestion is capable of significantly reducing organic pollutant loads, such as biochemical oxygen demand and chemical oxygen demand, while simultaneously producing biogas as a renewable energy source. The application of this technology supports environmentally friendly waste management practices and contributes to resource recovery. Furthermore, the integration of anaerobic digestion systems has the potential to improve production efficiency, reduce water and energy consumption, and minimize adverse health impacts associated with water pollution. The development and implementation of modern monitoring systems can further enhance process stability, optimize fermentation performance, and improve the accuracy of biodigester operation control. Overall, anaerobic digestion represents an effective, strategic, and sustainable solution for managing tofu industry wastewater and promoting healthier environmental development.